2018
DOI: 10.1007/s00894-018-3718-4
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of pyrazole derivatives with halomethanes: A DFT theoretical study

Abstract: The N-alkylation reaction of pyrazole derivatives with halomethanes was studied using density functional theory (DFT). The hybrid method B3LYP was employed, along with an ECP basis set such as LANL2DZ for halogen atoms (X = Cl, Br, I) and the 6-311 + G(d,p) basis set for all other atoms. In order to predict the specific site at which the pyrazole derivatives interact with halomethanes, local reactivity descriptors such as the Fukui functions were calculated. Detailed analysis of transition-state energies showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Also, CH 2 Cl 2 is the most inactive molecule for halogen bonding capability and mostly form hydrogen bonds as described by Ivanov et al 23 For such inactive halomethanes to form a halogen bond, electron-rich molecules are required. Theoretical studies of pyrazole molecules have been carried out 22 where electrostatic surface potential (ESP) distribution of pyrazole molecules showed that most negative potential occurs at the N atom, which may add significant contribution for inactive haloalkanes to form halogen bonding interactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Also, CH 2 Cl 2 is the most inactive molecule for halogen bonding capability and mostly form hydrogen bonds as described by Ivanov et al 23 For such inactive halomethanes to form a halogen bond, electron-rich molecules are required. Theoretical studies of pyrazole molecules have been carried out 22 where electrostatic surface potential (ESP) distribution of pyrazole molecules showed that most negative potential occurs at the N atom, which may add significant contribution for inactive haloalkanes to form halogen bonding interactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Geometry optimizations were performed at the PBE0-D3(BJ)/def2-SVP level 56-57-58 . Transition state structures were obtained using the intrinsic reaction coordinate [59][60] (IRC) method. Frequency calculations were performed on all stationary points, no imaginary frequencies were observed for the minima, and a single imaginary frequency corresponding to the reaction coordinate was found for all transition states (TSs).…”
Section: -(4-methylthiazol-5-yl)benzonitrile (Cd3)mentioning
confidence: 99%
“…The molecular electrostatic potential (MEP) has been used as a qualitative tool for identifying molecular regions susceptible to electrophilic or nucleophilic attack, and for analyzing and predicting noncovalent interactions [70][71][72][73]. The electrostatic potential maps are color-coded and are subdivided into many regions where those various colors are used to identify different potentials.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%